Medication Overuse Headache: A Trap for the Headache Patients - Rahman, A; Habib, R; Bhowmik, NB; Haque, A (BIRDEM Medical Journal, 2013)
Medication Overuse Headache (MOH) was previously termed analgesic rebound headache, drug-induced headache, and medication-misuse headache. It is not a primary headache but frequently coexists with primary chronic daily headache. All acute symptomatic medications used to treat headaches have the potential for causing MOH. Highest with opioids, butalbital-containing combination analgesics, and aspirin/ acetaminophen/caffeine combinations. The development is typically preceded by an episodic headache disorder, usually migraine or tension-type headache, that has been treated with frequent and excessive amounts of acute symptomatic medications. The diagnosis is based upon clinical impression. A history of analgesic use averaging more than two to three days per week in association with chronic daily headache is suggestive. The diagnosis is made when the pattern of frequent headaches fulfills the diagnostic criteria for MOH. The basic steps in the management: Patient education, withdrawal of the offending medication, bridge (transitional) therapy, establishment of a headache treatment regimen covering acute and preventive care, follow up and relapse prevention. Birdem Med J 2013; 3(2): 94-98 DOI: http://dx.doi.org/10.3329/birdem.v3i2.17213